Negative electrode active material, method for preparing negative electrode active material, negative electrode composition, negative electrode for lithium secondary battery comprising same, and lithium secondary battery comprising negative electrode
By forming a silicon oxide coating with high oxygen content on the surface of the silicon-based active material and adjusting the grain size and specific surface area of the material, the volume expansion of the silicon-based active material and uneven electrode coating in lithium secondary batteries is solved. The problem is that the service life and capacity characteristics of the electrode are improved.
Patent Information
- Application Number
- CN202380046409.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-07
AI Technical Summary
When using silicon-based active material as the negative electrode active material, volume expansion during charge and discharge leads to damage to the conductive path, and during the slurry preparation, the electrode coating is uneven and the service life characteristics are deteriorated.
Silicon-based active materials are prepared by chemical methods, and a silicon oxide coating containing more than 40% oxygen atoms is formed on its surface to inhibit reaction with solvents and gas generation, while adjusting the grain size and specific surface area of the silicon-based active materials. To reduce stress and particle rupture.
When using silicon-based active materials in lithium secondary batteries, it is possible to reduce the conduction path failure caused by volume expansion, improve the service life stability and capacity characteristics of the electrode, and reduce the problem of uneven electrode coating.
Smart Images

Figure CN119404329A_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0110091 filed in the Korean Intellectual Property Office on August 31, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode active material, a method for preparing the negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode composition, and a lithium secondary battery comprising the negative electrode. Background Art
[0003] Due to the rapid growth in the use of fossil fuels, the demand for the use of alternative or clean energy is increasing, and as part of this trend, the most active research area is the field of power generation and storage using electrochemical reactions.
[0004] Currently, representative examples of electrochemical devices using such electrochemical energy include secondary batteries, and their fields of use are increasingly expanding.
[0005] With the technological development and increased demand for mobile devices, the demand for secondary batteries as energy sources has grown rapidly. Among these secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, research on the preparation method of high-density electrodes with higher energy density per unit volume has been actively carried out.
[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material that intercalates and deintercalates lithium ions from the positive electrode, and as the negative electrode active material, silicon-based particles having a high discharge capacity can be used.
[0007] In particular, with the recent growth in demand for high-density energy batteries, research has been actively conducted on methods of increasing capacity by using silicon-based compounds such as Si / C or SiOx, which have a capacity 10 times or more that of graphite-based materials, as negative electrode active materials. Although silicon-based compounds as high-capacity materials have a higher capacity than graphite used in the prior art, they have a problem of rapidly expanding in volume during charging, thereby disconnecting the conductive path and causing deterioration of battery characteristics.
[0008] Therefore, in order to solve the problem when silicon-based compounds are used as negative electrode active materials, measures for adjusting the driving potential have been discussed, as well as measures for suppressing their own volume expansion such as a method of further coating the active material layer with a thin film and a method of adjusting the particle size of the silicon-based compound, various measures to prevent the conductive path from being disconnected, etc. However, there are limitations on the application of the above measures because the performance of the battery may deteriorate. Therefore, there are still limitations on the commercial preparation of batteries with a high content of silicon-based compounds in the negative electrode.
[0009] In addition, although research has been conducted to reduce the electrode resistance of electrodes using silicon-based compounds to ensure service life stability, in the preparation of slurries containing silicon-based active materials, there are still problems such as gas generation due to reaction with solvents, resulting in problems such as uneven electrode coating and deterioration of service life characteristics.
[0010] Therefore, there is a need to study a silicon-based active material which can prevent the destruction of the conductive path due to volume expansion of the silicon-based compound and suppress gas generation at the time of slurry formation even when used as a negative electrode active material to improve capacity performance.
[0011] <Prior Art Literature>
[0012] (Patent Document 1) Japanese Patent Publication No. 2009-080971 Summary of the invention
[0013] [Technical issues]
[0014] When a silicon-based active material is prepared using a chemical processing method instead of the existing pulverization processing method, the physical properties of the silicon-based active material itself can be adjusted, thereby confirming that during the insertion / deinsertion reaction of lithium, the reaction occurs uniformly and the stress applied to the silicon-based active material is reduced. However, even in this case, the generation of gas due to the reaction between silicon and the slurry solvent during slurry preparation becomes a problem, and it has been found that when a coating having a specific composition is formed on the silicon-based active material prepared as described above, such a problem can be solved.
[0015] Therefore, the present application relates to a negative electrode active material capable of solving the above problems, a method for preparing the negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode composition, and a lithium secondary battery comprising the negative electrode.
[0016] [Technical solution]
[0017] An exemplary embodiment of the present specification provides a negative electrode active material, which includes: a silicon-based active material; and a silicon oxide coating surrounding at least a part of the outer surface of the silicon-based active material, wherein, based on 100% of all atoms contained in the silicon oxide coating, the content of oxygen (O) atoms in the silicon oxide coating is 40% or more, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 70 parts by weight or more.
[0018] Another exemplary embodiment provides a method for preparing a negative electrode active material, the method including: depositing a silicon-based active material on a substrate through a chemical reaction of a silane gas; obtaining the silicon-based active material deposited on the substrate; and forming a silicon oxide on the surface of the silicon-based active material, wherein the forming of the silicon oxide includes: oxidizing the silicon-based active material through heat treatment or chemical treatment; or coating the surface of the silicon-based active material with a silicon oxide, the negative electrode active material includes a silicon oxide coating surrounding at least a part of the outer surface of the silicon-based active material, and based on 100% of all atoms contained in the silicon oxide coating, the content of oxygen (O) atoms in the silicon oxide coating is 40% or more.
[0019] Yet another exemplary embodiment aims to provide a negative electrode composition, which includes: the negative electrode active material according to the present application; a negative electrode conductive material; and a negative electrode binder.
[0020] Yet another exemplary embodiment aims to provide a negative electrode for a lithium secondary battery, the negative electrode including: a negative electrode current collector layer; and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer includes the negative electrode composition according to the present application or a cured product thereof.
[0021] Finally, a lithium secondary battery is provided, the battery including: a positive electrode; the negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
[0022] [Advantageous Effects]
[0023] The negative electrode active material of the present invention contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2) as the silicon-based active material, and contains 70 parts by weight or more of SiOx (x = 0), that is, a pure Si active material, based on 100 parts by weight of the silicon-based active material. The negative electrode active material is produced by controlling the reaction conditions of a chemical method, different from the existing comminution processing method, and thus, the negative electrode active material of the present invention contains a silicon-based active material satisfying predetermined physical properties. When the silicon-based active material prepared as described above is used, a uniform reaction can be carried out during the insertion and extraction reactions of lithium during charge and discharge, and the stress applied to the silicon-based active material can be reduced to alleviate particle breakage, thereby improving the service life retention rate of the electrode.
[0024] In addition, the present application is characterized in that a silicon oxide coating under specific conditions is formed on at least a part of the outer surface of the silicon-based active material prepared as described above. Therefore, the silicon oxide coating serves as a protective layer for preventing hydrogen generation reactions by suppressing the reaction between the surface of the silicon-based active material and the solvent during slurry formation, and has the characteristic of being able to alleviate the unevenness of electrode coating caused by bubble generation during electrode coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 FIG. is a view showing a laminated structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0026] Figure 2 FIG. is a view showing a laminated structure of a lithium secondary battery according to an exemplary embodiment of the present application.
[0027] Figure 3 FIG. is a view showing a method for calculating the grain size.
[0028] <Reference Numerals>
[0029] 10: Negative electrode current collector layer
[0030] 20: Negative electrode active material layer
[0031] 30: Separator
[0032] 40: Positive electrode active material layer
[0033] 50: Positive electrode current collector layer
[0034] 100: Negative electrode for lithium secondary battery
[0035] 200: Positive electrode for lithium secondary battery DETAILED DESCRIPTION OF THE EMBODIMENTS
[0036] Before describing the present invention, some terms will first be defined.
[0037] In the present specification, when a part “comprises” a constituent element, unless otherwise specifically described, this does not mean that other constituent elements are excluded but means that other constituent elements may further be included.
[0038] In this specification, 'p to q' means a range of 'not less than p and not more than q'.
[0039] In this specification, the "specific surface area" is measured by the BET method, and specifically is calculated based on the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSORP-mini II manufactured by BEL Japan. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the measurement method.
[0040] In this specification, "Dn" refers to particle size distribution, and refers to the particle size at n% point of the cumulative distribution of the number of particles corresponding to the particle size. That is, D50 is the particle size (average particle size) at 50% point of the cumulative distribution of the number of particles corresponding to the particle size, D90 is the particle size at 90% point of the cumulative distribution of the number of particles corresponding to the particle size, and D10 is the particle size at 10% point of the cumulative distribution of the number of particles corresponding to the particle size. On the other hand, the average particle size can be measured by laser diffraction. Specifically, after the powder to be measured is dispersed in a dispersion medium, the generated dispersion is introduced into a commercially available laser diffraction particle size measuring device (such as Microtrac S3500), and the difference in the diffraction pattern corresponding to the particle size is measured when the particle passes through the laser beam to calculate the particle size distribution.
[0041] In an exemplary embodiment of the present application, the particle size or particle diameter may refer to an average diameter or a representative diameter of each particle forming the metal powder.
[0042] In the present specification, the fact that a polymer contains a monomer as a monomer unit means that the monomer participates in a polymerization reaction and is thereby contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, the interpretation is the same as when the polymer contains a monomer as a monomer unit.
[0043] In this specification, the term 'polymer' is understood to be used in a broad sense including copolymers, unless otherwise explicitly indicated as a 'homopolymer'.
[0044] In this specification, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are polystyrene-converted molecular weights measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various degrees of polymerization for measuring molecular weights as standard materials. In this specification, unless otherwise described, the molecular weight refers to the weight-average molecular weight.
[0045] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings, so that those of ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, the present invention can be implemented in many different forms and is not limited to the following description.
[0046] An exemplary embodiment of this specification provides a negative electrode active material, which includes: a silicon-based active material; and a silicon oxide coating surrounding at least a part of the outer surface of the silicon-based active material, wherein, based on 100% of all atoms contained in the silicon oxide coating, the oxygen (O) atom content in the silicon oxide coating is 40% or more, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 70 parts by weight or more.
[0047] The negative electrode active material according to the present application includes a silicon oxide coating surrounding at least a part of the surface of the silicon-based active material prepared by a specific preparation method. Therefore, the silicon oxide coating serves as a protective layer that prevents the hydrogen generation reaction by suppressing the reaction between the surface of the silicon-based active material and the solvent during slurry formation, and has the characteristic of being able to reduce the unevenness of electrode coating caused by bubble generation during electrode coating.
[0048] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the thickness of the silicon oxide coating is 1 nm or more and 3 μm or less.
[0049] In another exemplary embodiment, the thickness of the silicon oxide coating can be 1 nm or more and 3 μm or less, preferably 2 nm or more and 3 μm or less, more preferably 3 nm or more and 3 μm or less.
[0050] When the thickness of the silicon oxide coating satisfies the above range, the contact between the solvent and the silicon-based active material can be easily prevented, and by having the above thickness range, the content of the silicon-based active material can also be maximized, so that the negative electrode active material has excellent capacity characteristics.
[0051] That is, when a slurry made of the silicon-based active material is formed, a SiOx layer is formed by a reaction between silicon on the particle surface and OH ions in the slurry solvent, while generating hydrogen, and when such a layer is formed thickly within the active material due to low conductivity, the resistance of the active material itself becomes high, thereby deteriorating the service life retention performance due to high resistance. The main feature of the present application is that a silicon oxide layer having the above-mentioned thickness range is easily and intentionally formed during the preparation process of the silicon-based active material, thereby solving the problem of deterioration of the service life retention performance as described above.
[0052] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the configuration area of the silicon oxide coating layer is 90% or more based on the outer surface of the silicon-based active material.
[0053] The configuration area may refer to the extent to which the silicon oxide coating is applied based on the outer surface of the silicon-based active material. That is, when the silicon oxide coating completely surrounds the silicon-based active material, the configuration area may be 100%, which may mean that the surface of the silicon-based active material may be disconnected from the outside, i.e., disconnected by the silicon oxide coating.
[0054] In an exemplary embodiment of the present application, based on the outer surface of the silicon-based active material, the configuration area of the silicon oxide coating can be greater than 90%, greater than 91%, or greater than 92%, and based on the outer surface of the silicon-based active material, it can satisfy the range of less than 100%, less than 99%, or less than 95%.
[0055] By having the silicon oxide coating configuration area as described above, gas generation can be more easily suppressed, and when included in an electrode later, the silicon oxide coating has a feature that can promote the function as a silicon-based active material. In particular, the silicon oxide coating according to the present application is used to obtain the effect of suppressing gas generation, and when the configuration area of the silicon oxide coating is 100%, the silicon oxide coating according to the present application has a feature that can reduce gas generation because it can block contact with water in a slurry state.
[0056] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon oxide coating layer includes one or more selected from the group consisting of crystalline silicon and amorphous silicon.
[0057] In an exemplary embodiment of the present application, the silicon oxide coating layer includes crystalline silicon.
[0058] In an exemplary embodiment of the present application, the silicon oxide coating layer includes amorphous silicon.
[0059] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein based on 100% of all atoms contained in the silicon oxide coating, the oxygen (O) atom content in the silicon oxide coating is 40% or more.
[0060] In another exemplary embodiment, based on 100% of all atoms contained in the silicon oxide coating, the oxygen (O) atom content in the silicon oxide coating is 40% or more, preferably 40.5% or more, more preferably 41% or more, and based on 100% of all atoms contained in the silicon oxide coating, it can satisfy the ranges of 70% or less, 50% or less, and 45% or less.
[0061] The oxygen (O) atom content in the silicon oxide coating may refer to the content of oxygen atoms when all atoms contained in the entire silicon oxide are defined as 100%. Specifically, the silicon oxide coating may contain oxygen and silicon atoms, and the oxygen (O) atom content in the silicon oxide coating may refer to the content of oxygen atoms when the sum of oxygen and silicon atoms is defined as 100%.
[0062] When the oxygen atom content in the silicon oxide coating is within the above range, the silicon oxide coating satisfies the above composition, and thus has the characteristic of being able to easily block OH ions of the silicon-based active material and the external slurry solvent. In particular, when the ratio of O in SiO2 to the silicon oxide coating itself is less than the above range, this may lead to a problem that defects may relatively increase.
[0063] In an exemplary embodiment of the present application, the silicon-based active material contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, it may contain 70 parts by weight or more of SiOx (x = 0).
[0064] In an exemplary embodiment of the present application, the silicon-based active material contains SiOx (x = 0), and based on 100 parts by weight of the silicon-based active material, it may contain 70 parts by weight or more of the SiOx (x = 0).
[0065] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0066] In an exemplary embodiment of the present application, the silicon-based active material, in particular, containing pure silicon (Si) particles, can be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material can mean that, as described above, based on a total of 100 parts by weight of the silicon-based active material, the amount of pure silicon particles (SiOx (x=0)) not combined with other particles or elements contained is within the above range.
[0067] In an exemplary embodiment of the present application, the silicon-based active material may be composed of silicon-based particles having 100 parts by weight of SiOx (x=0) based on 100 parts by weight of the silicon-based active material.
[0068] In an exemplary embodiment of the present application, the silicon-based active material may contain metal impurities. In this case, the impurities are metals that may be generally contained in the silicon-based active material, and the specific content may be less than 0.1 parts by weight based on 100 parts by weight of the silicon-based active material.
[0069] Since silicon-based active materials have significantly higher capacity than graphite-based active materials used in the prior art, attempts to use silicon-based active materials are increasing, but because silicon-based active materials have a high volume expansion rate during charge and discharge, the attempts are limited to situations where a small amount of silicon-based active materials is mixed with a graphite-based active material and used.
[0070] Therefore, the present invention solves the existing problems by adjusting the grain size or specific surface area of the silicon-based active material itself instead of adjusting the composition of the conductive material and the binder when only the silicon-based active material is used as the negative electrode active material to improve the capacity performance.
[0071] In an exemplary embodiment of the present application, the grain size of the silicon-based active material may be 200 nm or less.
[0072] In another exemplary embodiment, the grain size of the silicon-based active material may be 200 nm or less, preferably 130 nm or less, more preferably 110 nm or less, even more preferably 100 nm or less, specifically 95 nm or less, and more specifically 91 nm or less. The grain size of the silicon-based active material may be in the range of 10 nm or more, preferably 15 nm or more.
[0073] The silicon-based active material has the above-mentioned grain size, and the grain size of the silicon-based active material can be adjusted by changing the process conditions during the preparation process. In this case, by satisfying the above-mentioned range, the grain boundaries are widely distributed, so that during the lithium ion embedding, the lithium ions can enter evenly, which can reduce the stress applied when the lithium ions are embedded in the silicon particles, thereby reducing the rupture of the particles. As a result, the silicon-based active material has the characteristic of being able to improve the service life stability of the negative electrode. When the grain size exceeds the above-mentioned range, the grain boundaries in the particles are narrowly distributed. In this case, the lithium ions are unevenly embedded in the particles, and the stress caused by the ion embedding is large, causing the particles to rupture.
[0074] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon-based active material includes a crystal structure having a grain distribution of 1 nm or more and 200 nm or less, and the area ratio of the crystal structure is 5% or less based on the total area of the silicon-based active material.
[0075] In another exemplary embodiment, the area ratio of the crystal structure may be 5% or less or 3% or less, and may be 0.1% or more, based on the total area of the silicon-based active material.
[0076] That is, the grain size of the silicon-based active material according to the present application is 200 nm or less, and the size of each crystal structure is small, and the above-mentioned area ratio can be satisfied. Therefore, the distribution of the grain boundaries can be expanded, thereby demonstrating the above-mentioned effect.
[0077] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the number of crystal structures included in the silicon-based active material is 20 or more.
[0078] In another exemplary embodiment, the number of crystal structures included in the silicon-based active material may be 20 or more, 30 or more, or 35 or more, and may satisfy a range of 60 or less or 50 or less.
[0079] That is, as described above, when the grain size satisfies the above range and the number of crystal structures also satisfies the above range, the strength of the silicon-based active material itself has an appropriate range, so that the silicon-based active material has the characteristic of being able to impart flexibility when contained in an electrode, and also has the characteristic of being able to effectively suppress volume expansion.
[0080] In the present application, a grain refers to a crystal particle that is a collection of irregular shapes under a microscope in a metal or material, and the grain size may refer to the diameter of the observed grain particle. That is, in the present application, the grain size refers to the size of a domain that shares the same crystal orientation in a particle, and has a different concept from the particle size or particle diameter that represents the size of a material.
[0081] In an exemplary embodiment of the present application, the grain size can be calculated as a full width at half maximum (FWHM) value by XRD analysis. Specifically, Figure 3 shows the method for calculating grain size. Figure 3 In the above, the remaining values except L are measured by XRD analysis of the silicon-based active material, and the grain size can be measured by the Debey-Scherrer mathematical formula indicating that FWHM is inversely proportional to the grain size. In this case, the Debey-Scherrer mathematical formula is the same as the following mathematical formula 1-1.
[0082] [Mathematical formula 1-1]
[0083] FWHM=Kλ / LCosθ
[0084] In mathematical formula 1-1,
[0085] L is the grain size, K is a constant, θ is the Bragg angle, and λ refers to the wavelength of the X-ray.
[0086] Furthermore, the shapes of the crystal grains are various, so three-dimensional measurement can be performed, and the size of the crystal grains can generally be measured by the commonly used circle method and diameter measurement method.
[0087] The diameter measurement method can be performed as follows: 5 to 10 equilibrium lines each having a length of L mm are drawn on a micrograph of the particle to be measured, the number of crystals z on the lines is counted, and the number of crystals z is averaged. In this case, only those crystals that are entirely within the lines are counted, and those that cross the lines are not included. When the number of lines is defined as P and the magnification is defined as V, the average particle diameter can be calculated using the following mathematical formula 1-2.
[0088] [Mathematical formula 1-2]
[0089] Dm = (L*P*10 3 ) / (zV) (μm)
[0090] In addition, in the circle method, the average area of the grains can be obtained by drawing a circle of a predetermined diameter on a micrograph of the target particle and then using the number of grains entering the circle and the number of grains on the boundary line. The average particle area can be calculated using the following mathematical formula 1-3.
[0091] [Mathematical formula 1-3]
[0092] Fm = (Fk * 10 6 ) / ((0.67n + z) V 2 )(μm 2 )
[0093] In Mathematical Formula 1-3, Fm refers to the average particle area, Fk refers to the measurement area on the photograph, z refers to the number of particles entering the circle, n refers to the number of particles on the arc, and V refers to the magnification of the microscope.
[0094] In an exemplary embodiment of the present application, the negative electrode active material may include a specific surface area of 0.25 m 2 / g or more silicon-based active material.
[0095] In another exemplary embodiment, the specific surface area of the silicon-based active material may be 0.25 m 2 / g or more, preferably 0.28 m 2 / g or more, more preferably 0.30 m 2 / g or more, specifically 0.31 m 2 / g or more, more specifically 0.32 m 2 / g or more. The specific surface area of the silicon-based active material can meet 3 m 2 / g or less, preferably 2.5 m 2 / g or less, more preferably 2.2m 2 The specific surface area can be measured according to DIN 66131 (using nitrogen gas).
[0096] The silicon-based active material has the above-mentioned specific surface area, and the specific surface area of the silicon-based active material can be adjusted by changing the process conditions in the preparation process described later and the growth conditions of the silicon-based active material. That is, when the negative electrode active material is prepared using the preparation method according to the present application, the negative electrode active material has a larger specific surface area than particles with the same particle size due to the rough surface. In this case, since the bonding strength with the binder is improved by satisfying the above-mentioned range, the negative electrode active material has the characteristic of being able to reduce cracks in the electrode caused by repeated charge and discharge cycles.
[0097] In addition, during the insertion of lithium ions, lithium ions can enter uniformly, which can reduce the stress applied when lithium ions are inserted into silicon particles, thereby alleviating the rupture of the particles. As a result, the negative electrode has a feature that can improve the service life stability of the negative electrode. When the specific surface area is less than the above range, even when the particles have the same particle size, a smooth surface is formed, the bonding strength with the binder is deteriorated, and electrode cracks occur, and in this case, lithium ions are unevenly inserted into the particles, and the stress caused by ion insertion is large, so that the particles rupture.
[0098] In an exemplary embodiment of the present application, there is provided a negative electrode active material, wherein the silicon-based active material satisfies the range of the following Mathematical Formula 2-1.
[0099] [Mathematical formula 2-1]
[0100] X1 / Y1 ≤ 0.960
[0101] In mathematical formula 2-1,
[0102] X1 is the actual area of the silicon-based active material, and
[0103] Y1 refers to the area of spherical particles having the same circumference as the silicon-based active material.
[0104] The measurement of mathematical formula 2-1 can be performed using a particle image analyzer. Specifically, after the silicon-based active material according to the present application is spread on a glass plate by air jet, a shadow image of the spread silicon-based active material particles can be taken to determine the shape of 10,000 silicon-based active material particles in the photograph. In this case, mathematical formula 2-1 is a value representing the average value of 10,000 particles. According to mathematical formula 2-1 of the present application, it can be measured from the above image, and the above mathematical formula 2-1 can be represented by the circularity of the silicon-based active material. The circularity can also be expressed by the mathematical formula [4π*actual area of the silicon-based active material / (boundary) 2 ] to indicate.
[0105] In an exemplary embodiment of the present application, the circularity of the silicon-based active material may be, for example, 0.960 or less, for example, 0.957 or less. The circularity of the silicon-based active material may be 0.8 or more, for example, 0.9 or more, specifically 0.93 or more, more specifically 0.94 or more, for example, 0.941 or more.
[0106] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon-based active material satisfies the range of the following Mathematical Formula 2-2.
[0107] [Mathematical formula 2-2]
[0108] X2 / Y2 ≤ 0.995
[0109] In mathematical formula 2-2,
[0110] Y2 is the actual circumference of the silicon-based active material, and
[0111] X2 is the perimeter of the circumscribed pattern of the silicon-based active material.
[0112] The measurement of mathematical formula 2-2 can be performed using a particle image analyzer. Specifically, after the silicon-based active material according to the present application is spread on a glass plate by air jet, a shadow image of the spread silicon-based active material particles can be taken to determine the shape of 10,000 silicon-based active material particles in the photograph. In this case, mathematical formula 2-2 is a value representing the average value of 10,000 particles. According to mathematical formula 2-2 of the present application, it can be measured from the above image, and the above mathematical formula 2-2 can be represented by the convexity of the silicon-based active material.
[0113] In an exemplary embodiment of the present application, X2 and Y2 may satisfy the range of X2 / Y2 ≤ 0.996, preferably the range of X2 / Y2 ≤ 0.995, and X2 and Y2 may satisfy the range of 0.8 ≤ X2 / Y2, preferably 0.9 ≤ X2 / Y2, more preferably 0.95 ≤ X2 / Y2, specifically 0.98 ≤ X2 / Y2.
[0114] The smaller the value of the above mathematical formula 2-1 or 2-2, the greater the roughness of the silicon-based active material may be, and since a silicon-based active material having a range as described above is used, the silicon-based active material has a characteristic of being able to reduce cracks in the electrode caused by repeated charge and discharge cycles due to an increase in the bonding strength with the binder.
[0115] In an exemplary embodiment of the present application, the silicon-based active material may include silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less.
[0116] The fact that the silicon-based active material includes silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less means that a large number of individual silicon-based particles having a particle size within the above range are included, and the number of silicon-based particles included is not limited.
[0117] When the silicon-based particles have a spherical shape, the particle size of the silicon-based particles can be expressed as the diameter of the silicon-based particles, but even in other non-spherical cases, the particle size can be measured by comparison with the spherical case, and the particle size of a single silicon-based particle can generally be measured by a measurement method in the art.
[0118] On the other hand, the average particle size (D50 particle size) of the silicon-based active material of the present invention can be 3 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is included in the above range, since the specific surface area of the particles is included in an appropriate range, the viscosity of the negative electrode slurry formed is within an appropriate range. Therefore, the dispersion of the particles constituting the negative electrode slurry is promoted. In addition, the size of the silicon-based active material has a value equal to or greater than the lower limit value range, and since the composite material composed of a conductive material and a binder in the negative electrode slurry makes the contact area between the silicon particles and the conductive material excellent, the possibility of the conductive network being continuous is increased, thereby increasing the capacity retention rate. On the other hand, when the average particle size satisfies the above range, excessively large silicon particles are excluded, thereby forming a smooth negative electrode surface, thereby preventing the phenomenon of uneven current density during charge and discharge.
[0119] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.01 to 150.0 m 2 / g, more preferably 0.1 to 100.0 m 2 / g, particularly preferably 0.2 to 80.0 m 2 / g, most preferably 0.2 to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).
[0120] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably non-porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a film or coating containing silicon.
[0121] In an exemplary embodiment of the present application, the silicon-based active material may have a non-circular shape, and its circularity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0122] In the present application, the circularity is determined by the following mathematical formula 3-1, where A is the area and P is the boundary line.
[0123] [Mathematical formula 3-1]
[0124] 4πA / P2
[0125] In an exemplary embodiment of the present application, a negative electrode composition is provided, the negative electrode composition including: a negative electrode active material; a negative electrode conductive material; and a negative electrode binder.
[0126] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the content of the negative electrode active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.
[0127] In another exemplary embodiment, the content of the negative electrode active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0128] The negative electrode composition according to the present application is characterized in that by using a negative electrode active material that satisfies a specific grain size, the volume expansion rate during charge and discharge can be suppressed even if a negative electrode active material with a significantly high capacity is used within the above range, and even if the above range is included, the performance of the negative electrode will not be deteriorated, and the output characteristics during charge and discharge are excellent.
[0129] In the prior art, only graphite compounds are generally used as negative electrode active materials, but recently, as the demand for high-capacity batteries increases, attempts to mix and use silicon compounds in order to increase capacity have been increasing. However, in the case of silicon-based active materials, even if the properties of the silicon-based active materials themselves are adjusted as described above, the volume expands rapidly during charge and discharge, so that in some cases, the problem of damage to the conductive path formed in the negative electrode active material layer may occur.
[0130] Therefore, in an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a planar conductive material, and a linear conductive material.
[0131] In an exemplary embodiment of the present application, the point-shaped conductive material can be used to improve the conductivity of the negative electrode, and refers to a point-shaped or spherical conductive material with conductivity that does not induce chemical changes. Specifically, the point-shaped conductive material can be at least one selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and can preferably contain carbon black in terms of achieving high conductivity and excellent dispersibility.
[0132] In an exemplary embodiment of the present application, the BET specific surface area of the dot-shaped conductive material may be 40 m 2 / g and above 70 m2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g or more and 60 m 2 / g or less.
[0133] In an exemplary embodiment of the present application, the functional group content (volatile matter) of the dot-shaped conductive material may satisfy 0.01% to 1%, preferably 0.01% to 0.3%, and more preferably 0.01% to 0.1%.
[0134] In particular, when the functional group content of the dot-shaped conductive material satisfies the above range, there are functional groups present on the surface of the dot-shaped conductive material, so that when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, in the present invention, since a specific silicon-based active material is used, the functional group content of the dot-shaped conductive material can be reduced, and therefore, the present invention has an excellent effect in improving dispersibility.
[0135] In an exemplary embodiment of the present application, it is characterized in that a dot-shaped conductive material having a functional group content within the above range is included together with the silicon-based active material, and the functional group content can be adjusted according to the degree of heat treatment of the dot-shaped conductive material.
[0136] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0137] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material.
[0138] The planar conductive material can improve conductivity by increasing surface contact between silicon particles in the negative electrode while suppressing disconnection of the conductive path due to volume expansion. The planar conductive material can be in the form of a plate-like conductive material or a bulk conductive material.
[0139] In an exemplary embodiment of the present application, the planar conductive material may include at least one selected from plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.
[0140] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 3.5 μm to 5 μm. When the average particle size satisfies the above range, sufficient particle size promotes dispersion without causing excessive increase in the viscosity of the negative electrode slurry. Therefore, when the same equipment and time are used to disperse the particles, the dispersion effect is excellent.
[0141] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the planar conductive material has a D10 of 0.5 μm to 2.0 μm, a D50 of 2.5 μm to 3.5 μm, and a D90 of 6.5 μm to 15.0 μm.
[0142] In an exemplary embodiment of the present application, as the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area; or a low specific surface area planar conductive material may be used.
[0143] In an exemplary embodiment of the present application, as the planar conductive material, a high specific surface area planar conductive material or a low specific surface area planar conductive material can be used without restriction, but in particular, the planar conductive material according to the present application may affect the electrode performance to a certain extent due to the dispersion effect, and therefore it may be particularly ideal to use a low specific surface area planar conductive material that does not have dispersion problems.
[0144] In an exemplary embodiment of the present application, the BET specific surface area of the planar conductive material may be 1 m 2 / g or above.
[0145] In another exemplary embodiment, the BET specific surface area of the planar conductive material may be 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m 2 / g or less.
[0146] As the planar conductive material according to the present application, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used.
[0147] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 300 m 2 / g or less.
[0148] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g or more and 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.
[0149] As other conductive materials, there may be linear conductive materials, such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specifically stated, the term 'bundle-type' used herein refers to a secondary shape in which a plurality of carbon nanotube units are arranged side by side or interwoven in a bundle or rope-like shape in an orientation substantially the same as the long axis of the carbon nanotube unit. In the carbon nanotube unit, the graphite sheet has a cylindrical shape with a nanometer-sized diameter and has an sp2 bonding structure. In this case, the carbon nanotube unit may exhibit the characteristics of a conductor or a semiconductor depending on the structure and angle of the curling of the graphite sheet. Compared with the entangled carbon nanotubes, the bundle-type carbon nanotubes may be uniformly dispersed during the preparation of the negative electrode, and the conductivity of the negative electrode may be improved by smoothly forming a conductive network in the negative electrode.
[0150] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the content of the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0151] In another exemplary embodiment, the content of the negative electrode conductive material may be 0.1 parts by weight or more and 40 parts by weight or less, preferably 0.2 parts by weight or more and 30 parts by weight or less, more preferably 0.4 parts by weight or more and 25 parts by weight or less, and most preferably 0.4 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0152] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode conductive material includes a planar conductive material and a linear conductive material.
[0153] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode conductive material comprises a planar conductive material and a linear conductive material, and based on 100 parts by weight of the negative electrode conductive material, the amount of the planar conductive material and the linear conductive material are respectively 80 parts by weight or more and 99.9 parts by weight or less and 0.1 parts by weight or more and 20 parts by weight or less.
[0154] In another exemplary embodiment, the negative electrode conductive material may include the planar conductive material in an amount of 80 parts by weight to 99.9 parts by weight, preferably 85 parts by weight to 99.9 parts by weight, and more preferably 95 parts by weight to 98 parts by weight, based on 100 parts by weight of the negative electrode conductive material.
[0155] In yet another exemplary embodiment, the negative electrode conductive material may include the linear conductive material in an amount of 0.1 parts by weight to 20 parts by weight, preferably 0.1 parts by weight to 15 parts by weight, and more preferably 0.2 parts by weight to 5 parts by weight, based on 100 parts by weight of the negative electrode conductive material.
[0156] In an exemplary embodiment of the present application, since the negative electrode conductive material includes a planar conductive material and a linear conductive material and the planar conductive material and the linear conductive material each satisfy the composition and ratio, the negative electrode conductive material has the following characteristics: because it has no significant impact on the service life characteristics of existing lithium secondary batteries, and especially when it includes a planar conductive material and a linear conductive material, the number of points in the battery that can be charged and discharged increases, so the output characteristics at a high C rate are excellent and the amount of high-temperature gas generated is reduced.
[0157] In an exemplary embodiment of the present application, the negative electrode conductive material may be composed of a linear conductive material.
[0158] In particular, when the linear conductive material is used alone, the electrode twisting property, which is a problem of the silicon-based negative electrode, can be simplified, thereby improving the electrode structure, and therefore, the negative electrode conductive material has a feature of being able to reduce the movement resistance of lithium ions in the electrode.
[0159] In an exemplary embodiment of the present application, when the negative electrode conductive material contains only the linear conductive material, the content of the negative electrode conductive material may be 0.1 parts by weight or more and 5 parts by weight or less, preferably 0.2 parts by weight or more and 3 parts by weight or less, and more preferably 0.4 parts by weight or more and 1 part by weight or less, based on 100 parts by weight of the negative electrode composition.
[0160] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material used for the positive electrode. That is, the negative electrode conductive material according to the present application plays a role in capturing the contact points between the silicon-based active materials whose electrode volume expands greatly due to charge and discharge, while the positive electrode conductive material plays a role in imparting partial conductivity and plays a buffering role due to the lining effect during rolling. Its structure and role are completely different from those of the negative electrode conductive material of the present invention.
[0161] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different structure from the conductive material applied to the graphite-based active material. That is, the conductive material used for the electrode with the graphite-based active material simply has particles smaller than the active material, thereby having the characteristics of improving the output characteristics and imparting partial conductivity, and its structure and function are completely different from the negative electrode conductive material applied with the silicon-based active material as in the present invention.
[0162] In an exemplary embodiment of the present application, the planar conductive material used as the above-mentioned negative electrode conductive material has a structure and function different from the carbon-based active material commonly used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material can be artificial graphite or natural graphite, and refers to a material processed into a spherical or dot-like shape for use to promote the storage and release of lithium ions.
[0163] On the other hand, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the plate-like conductive material is a material contained in order to maintain a conductive path in the negative electrode active material layer, and refers to a material that ensures a conductive path in a planar form within the negative electrode active material layer rather than a material that functions to store and release lithium.
[0164] That is, in the present application, the fact that plate-like graphite is used as a conductive material means that the plate-like graphite is processed into a planar or plate-like shape and used as a material that ensures a conductive path rather than a function of storing or releasing lithium. In this case, the negative electrode active material contained together has a high capacity characteristic for storing and releasing lithium, and plays a role of being able to store and release all lithium ions transferred from the positive electrode.
[0165] On the other hand, in the present application, the fact that a carbon-based active material is used as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.
[0166] That is, in an exemplary embodiment of the present application, artificial graphite or natural graphite as a carbon-based active material is dot-shaped, and its BET specific surface area may satisfy 0.1 m 2 / g and above 4.5 m2 In addition, the plate-like graphite as a planar conductive material is planar, and its BET specific surface area can be 5m 2 / g or above.
[0167] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials in which hydrogen is replaced by Li, Na, Ca, etc., and various polymers thereof may also be included.
[0168] The negative electrode binder according to an exemplary embodiment of the present application plays a role in supporting the active material and the conductive material to prevent the distortion and structural deformation of the negative electrode structure when the volume of the silicon-based active material expands and relaxes. When the above-mentioned role is met, all general negative electrode binders can be applied, specifically, aqueous binders can be used, and more specifically, PAM-based binders can be used.
[0169] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may be 5 parts by weight or more and 10 parts by weight or more, based on 100 parts by weight of the negative electrode composition.
[0170] An exemplary embodiment of the present application provides a method for preparing a negative electrode active material, the method comprising: depositing a silicon-based active material onto a substrate through a chemical reaction of silane gas; obtaining the silicon-based active material deposited on the substrate; and forming silicon oxide on the surface of the silicon-based active material, wherein the formation of the silicon oxide comprises: oxidizing the silicon-based active material through heat treatment or chemical treatment; or coating the surface of the silicon-based active material with silicon oxide, and comprising a silicon oxide coating surrounding at least a portion of the outer surface of the silicon-based active material.
[0171] In this case, the method of forming the silicon oxide coating layer may include: oxidizing the silicon-based active material through heat treatment or chemical treatment; or coating the surface of the silicon-based active material with silicon oxide.
[0172] The oxidation of the silicon-based active material by heat treatment or chemical treatment corresponds to the existing method of oxidizing the surface of silicon-based active material particles. Specifically, the oxidation of the silicon-based active material by heat treatment can be carried out by heat treatment at 40°C to 1000°C for 1 minute to 90 minutes while oxygen is flowing to form a silicon oxide coating. In addition, the oxidation of the silicon-based active material by heat treatment can be carried out not only by the method described above, but also by heating the silicon-based active material to a temperature of 300°C to 1000°C in a mixed gas of inert gas and oxygen to form a silicon oxide coating.
[0173] In addition, for the oxidation of the silicon-based active material by chemical treatment, the silicon oxide coating can be formed by treating the silicon-based active material with 30 volume % H2O2 hydrogen peroxide + 70 volume % H2SO4 sulfuric acid (piranha solution) or high concentration nitric acid.
[0174] The surface of the silicon-based active material is coated with silicon oxide, which is not derived from the existing silicon-based active material, but is coated with a new silicon oxide coating, and the silicon oxide coating can be formed on the surface by a hydration process of tetraethyl orthosilicate using an alkaline material in a state where tetraethyl orthosilicate and the silicon-based active material are mixed.
[0175] According to the above method, the negative electrode active material according to the present application has a feature of being able to manufacture an electrode that generates less gas during slurry formation and has excellent lifespan characteristics.
[0176] In an exemplary embodiment of the present application, a method for preparing a negative electrode active material is provided, wherein the heat treatment of the silicon-based active material is performed under the condition of 40° C. or higher and 150° C. or lower.
[0177] By satisfying the temperature conditions as described above, a silicon oxide coating layer having a thin thickness range can be intentionally formed, and the above-mentioned problems are solved by the silicon oxide coating layer formed under the conditions as described above.
[0178] According to one example, the silane gas may include one or more gases selected from monosilane, dichlorosilane, and trichlorosilane, and may specifically be trichlorosilane gas.
[0179] In the present application, a method for preparing a negative electrode active material is provided, wherein the deposition of the silicon-based active material onto a substrate through a chemical reaction of silane gas is performed under high temperature conditions above 100°C.
[0180] In an exemplary embodiment of the present application, the deposition of the silicon-based active material onto the substrate by chemical reaction of silane gas can be performed under a pressure condition of 10 Pa to 150 Pa. The low pressure as described above can reduce the silicon growth rate, thereby achieving the formation of small grains. The step can be performed at a temperature of 100°C or more, specifically 500°C or more, preferably 800°C or more, more preferably 800°C to 1300°C, or 800°C to 1100°C. This is lower than the temperature of the existing gas atomization method of heating Si to 1,600°C or more to melt Si.
[0181] In an exemplary embodiment of the present application, the method may further include growing the silicon-based active material by crystal nucleation, and the growing of the silicon-based active material by crystal nucleation may be performed at a temperature of 800°C or more, preferably 800°C to 1300°C. This is lower than the temperature of the existing gas atomization method of heating Si to above 1,600°C to melt Si. In addition, the growing of the silicon-based active material by crystal nucleation may be performed at a pressure of 100 Pa to 150 Pa. The low pressure as described above can reduce the silicon growth rate, thereby achieving the formation of small grains and a specific surface area.
[0182] In the prior art, the negative electrode active material is prepared by crushing silicon blocks by physical force. When the negative electrode active material is prepared as described above, the size of the grains is generally greater than 200 nm and the surface is smooth, so that the specific surface area is less than 0.25 m 2 When the silicon-based active material is prepared simply by the method in the prior art, the specific surface area cannot be controlled, so there is a disadvantage that it is difficult to ensure the service life stability of the negative electrode.
[0183] However, the method for preparing negative electrode active materials according to the present application can be formed by including silane gasification of silicon blocks through chemical reaction under the specific process conditions as described above, and then growing silicon-based active materials through crystal nucleation to form silicon particles, thereby obtaining silicon-based active materials that meet the specific surface area and grain size according to the present application.
[0184] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, the negative electrode comprising: a negative electrode collector layer; and a negative electrode active material layer formed on one surface or both surfaces of the negative electrode collector layer, the negative electrode active material layer comprising the negative electrode composition according to the present application or a cured product thereof.
[0185] Figure 11 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be confirmed that the negative electrode for a lithium secondary battery 100 includes a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10, Figure 1 The negative electrode active material layer formed on one surface is shown, but the negative electrode active material layer may be contained on both surfaces of the negative electrode collector layer.
[0186] In an exemplary embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry including the negative electrode composition to one surface or both surfaces of the negative electrode collector layer and drying the negative electrode slurry.
[0187] In this case, the negative electrode slurry may include: the negative electrode composition described above; and a slurry solvent.
[0188] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy 5% or more and 40% or less.
[0189] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.
[0190] The solid content of the negative electrode slurry may refer to the content of the negative electrode composition contained in the negative electrode slurry, and may refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0191] When the solid content of the negative electrode slurry satisfies the above range, the present invention has a feature of being able to effectively form a negative electrode active material layer by minimizing a particle aggregation phenomenon of the negative electrode composition because the viscosity is appropriate during the formation of the negative electrode active material layer.
[0192] In an exemplary embodiment of the present application, the slurry solvent may be used without limitation as long as the slurry solvent can dissolve the negative electrode composition, but specifically, water or NMP may be used.
[0193] In an exemplary embodiment of the present application, the thickness of the negative electrode collector layer is generally 1 μm to 100 μm. There is no particular limitation on the negative electrode collector layer, as long as the negative electrode collector layer has high conductivity and does not cause chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, materials for surface treatment of copper or stainless steel with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloys, etc. can be used. In addition, the negative electrode collector layer can also increase the bonding strength of the negative electrode active material by forming fine concave-convex on its surface, and the negative electrode collector layer can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0194] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the thickness of the negative electrode collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.
[0195] However, the thickness may be variously modified depending on the type and purpose of the negative electrode used, and is not limited thereto.
[0196] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.
[0197] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0198] The porosity varies depending on the composition and content of the silicon-based active material, conductive material and binder contained in the negative electrode active material layer. In particular, when the silicon-based active material and conductive material according to the present application are contained in a specific composition and content to meet the above-mentioned range, it is characterized in that the conductivity and resistance in the electrode have an appropriate range.
[0199] In an exemplary embodiment of the present application, a lithium secondary battery is provided, the lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0200] Figure 21 is a diagram showing a stacked structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, a negative electrode 100 for a lithium secondary battery including a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10 can be confirmed, and a positive electrode 200 for a lithium secondary battery including a positive electrode active material layer 40 on one surface of a positive electrode collector layer 50 can be confirmed, and the negative electrode 100 for a lithium secondary battery and the positive electrode 200 for a lithium secondary battery are formed to stack the electrodes with a separator 30 placed therebetween.
[0201] A secondary battery according to an exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described in detail, the specific description thereof will be omitted.
[0202] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0203] In the positive electrode, there is no particular limitation on the positive electrode collector, as long as the positive electrode collector has conductivity and does not cause chemical changes in the battery, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and the adhesion of the positive electrode active material can also be enhanced by forming fine concavoconvexities on the surface of the collector. For example, the positive electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0204] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or a compound substituted by one or more transition metals; a lithium iron oxide such as LiFe3O4; a compound having a chemical formula of Li 1+c1 Mn 2-c1 Lithium manganese oxides such as LiMnO4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; chemical formula LiNi 1-c2 M c2 Ni-site lithium nickel oxide represented by O2 (herein, M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B and Ga, and c2 satisfies 0.01≤c2≤0.6); chemical formula LiMn2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (herein, M is at least one selected from Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.6); LiMn2O4 in which Li in the chemical formula is partially replaced by alkaline earth metal ions, etc., but not limited thereto. The positive electrode may be Li metal.
[0205] In an exemplary embodiment of the present application, the positive electrode active material contains a lithium composite transition metal compound containing nickel (Ni), cobalt (Co) and manganese (Mn), the lithium composite transition metal compound contains single particles or secondary particles, and the average particle size (D50) of the single particles can be 1 μm or more.
[0206] For example, the average particle size (D50) of the single particles may be 1 μm to 12 μm, 1 μm to 8 μm, 1 μm to 6 μm, greater than 1 μm to 12 μm, greater than 1 μm to 8 μm, or greater than 1 μm to 6 μm.
[0207] Even if the single particle is formed into a small particle size with an average particle size (D50) of 1 μm or more and 12 μm or less, the particle strength can be excellent. 2 The particle strength of the single particle can be 100 to 300 MPa when the force is extended. As a result, even at 650 kgf / cm 2 The strong calendering of the single particle also reduces the increase in the number of particles in the electrode due to particle fragmentation, thereby improving the service life characteristics of the battery.
[0208] The single particle may be prepared by mixing a transition metal precursor and a lithium raw material and firing the resulting mixture. The secondary particle may be prepared by a different method from the single particle, and its composition may be the same as or different from that of the single particle.
[0209] There is no particular limitation on the method for forming the single particles, but generally, single particles can be formed by increasing the firing temperature to achieve overfiring, and can be prepared by using additives that facilitate overfiring such as grain growth promoters or by changing starting materials.
[0210] For example, the calcination is carried out at a temperature capable of forming a single particle. In order to form a single particle, it is necessary to calcine at a temperature higher than that at which the secondary particles are prepared. For example, when the composition of the precursor is the same, it is necessary to calcine at a temperature of about 30°C to 100°C higher than that at which the secondary particles are prepared. The calcination temperature for forming a single particle may vary depending on the metal composition in the precursor. For example, when it is desired to form a high-nickel NCM lithium composite transition metal oxide having a nickel (Ni) content of more than 80 mol % as a single particle, the calcination temperature may be 700°C to 1000°C, preferably about 800°C to 950°C. When the calcination temperature satisfies the above range, a positive electrode active material comprising a single particle having excellent electrochemical properties can be prepared. When the calcination temperature is lower than 790°C, a positive electrode active material comprising a lithium composite transition metal compound in the form of a secondary particle can be prepared, and when the calcination temperature exceeds 950°C, over-calcination may occur, so that a layered crystal structure cannot be properly formed, thereby deteriorating the electrochemical properties.
[0211] In this specification, the single particle is a term used in the prior art to distinguish a single particle from a secondary particle formed by the aggregation of tens to hundreds of primary particles, and is a concept that includes a single particle composed of one primary particle and a quasi-single particle that is an aggregate of 30 or less primary particles.
[0212] Specifically, in the present invention, the single particle may be in the form of a single particle consisting of one primary particle or a quasi-single particle that is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of hundreds of primary particles.
[0213] In an exemplary embodiment of the present application, the lithium composite transition metal compound as the positive electrode active material further includes secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.
[0214] In the present invention, the single particle may be in the form of a single particle composed of one primary particle or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.
[0215] The lithium composite transition metal compound may further include secondary particles. The secondary particles are formed by aggregation of primary particles and can be distinguished from the concept of single particles including one primary particle, one single particle, or a quasi-single particle that is an aggregation of 30 or less primary particles.
[0216] The particle size (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, and preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles may be 0.05 m2 / g to 10 m 2 / g, preferably 0.1 m 2 / g to 1 m 2 / g, more preferably 0.3 m 2 / g to 0.8 m 2 / g.
[0217] In another exemplary embodiment of the present application, the secondary particles are aggregates of primary particles, and the average particle size (D50) of the primary particles is 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of hundreds of primary particles aggregated, and the average particle size (D50) of the primary particles may be 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.
[0218] When the average particle size (D50) of the primary particles satisfies the above range, a single-particle positive electrode active material with excellent electrochemical properties can be formed. When the average particle size (D50) of the primary particles is too small, the number of primary particles that form lithium nickel oxide particles increases, thereby reducing the effect of suppressing particle breakage during rolling, and when the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles becomes longer, thereby increasing resistance and possibly deteriorating output characteristics.
[0219] According to another exemplary embodiment of the present application, the average particle size (D50) of the single particle is characterized by being smaller than the average particle size (D50) of the secondary particle. Therefore, even if the single particle is formed into a small particle size, the single particle can still have excellent particle strength, and the excellent particle strength can reduce the phenomenon of an increase in the number of particles in the electrode due to particle rupture, thereby improving the service life characteristics of the battery.
[0220] In an exemplary embodiment of the present application, an average particle diameter (D50) of the single particles is 1 μm to 18 μm smaller than an average particle diameter (D50) of the secondary particles.
[0221] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm, 1.5 μm to 15 μm, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.
[0222] When the average particle size (D50) of the single particle is smaller than the average particle size (D50) of the secondary particle, for example, when the above range is met, the single particle can have excellent particle strength even if it is formed into a small particle size. Thus, the excellent particle strength reduces the phenomenon of an increase in the number of particles in the electrode due to particle breakage, thereby improving the service life characteristics of the battery and improving the energy density.
[0223] According to another exemplary embodiment of the present application, the content of the single particle is 15 to 100 parts by weight relative to 100 parts by weight of the positive electrode active material. The content of the single particle may be 20 to 100 parts by weight, or 30 to 100 parts by weight relative to 100 parts by weight of the positive electrode active material.
[0224] For example, the content of the single particle may be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more relative to 100 parts by weight of the positive electrode active material. The content of the single particle may be 100 parts by weight or less relative to 100 parts by weight of the positive electrode active material.
[0225] When the single particles within the above range are included, the combination with the above negative electrode material can exhibit excellent battery characteristics. In particular, when the amount of the single particles is 15 parts by weight or more, the phenomenon of increasing the number of particles in the electrode due to particle rupture during the rolling process after electrode manufacturing can be reduced, thereby improving the service life characteristics of the battery.
[0226] In an exemplary embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the amount of the secondary particles may be 85 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The amount of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The amount of the secondary particles may be 0 parts by weight or more relative to 100 parts by weight of the positive electrode active material.
[0227] When the above range is met, the above effect due to the presence of a single particle of positive electrode active material can be maximized. When a secondary particle of positive electrode active material is included, the component may be the same as the component exemplified as the above single particle positive electrode active material, or may be a different component, and may mean an aggregated form of a single particle form.
[0228] In an exemplary embodiment of the present application, in 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material may be greater than 80 parts by weight and less than 99.9 parts by weight, preferably greater than 90 parts by weight and less than 99.9 parts by weight, more preferably greater than 95 parts by weight and less than 99.9 parts by weight, and even more preferably greater than 98 parts by weight and less than 99.9 parts by weight.
[0229] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder as well as the positive electrode active material.
[0230] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity and does not cause chemical changes in the battery to be constituted. Specific examples thereof include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used.
[0231] In addition, the positive electrode binder plays a role in improving the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples thereof may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.
[0232] The separator separates the negative electrode from the positive electrode and provides a mobile path for lithium ions, and as long as the separator is generally used as a separator in a lithium secondary battery, it can be used without particular restriction, in particular, it is preferred that the separator has excellent electrolyte moisture-containing capacity and low resistance to the movement of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, a common porous nonwoven fabric can also be used, such as a nonwoven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a coated separator comprising a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.
[0233] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc. that can be used in the preparation of lithium secondary batteries, but are not limited thereto.
[0234] Specifically, the electrolyte may include a nonaqueous organic solvent and a lithium salt.
[0235] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.
[0236] In particular, among the carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate can be preferably used because the cyclic carbonates have a high dielectric constant as a high-viscosity organic solvent, thereby dissociating lithium salts well, and because the cyclic carbonates can be mixed with low-viscosity and low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in an appropriate ratio and used to prepare an electrolyte with high conductivity, such cyclic carbonates can be more preferably used.
[0237] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily dissolved in a non-aqueous electrolyte. For example, as the anion of the lithium salt, one or more selected from the following can be used: - , Cl- ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0238] In the electrolyte, in order to improve the battery life characteristics, inhibit the battery capacity reduction and improve the battery discharge capacity, in addition to the above-mentioned electrolyte constituent components, one or more additives may be included, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride.
[0239] An exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate properties and cycle properties, and can therefore be used as a power source for medium and large devices selected from electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0240] [Mode of invention]
[0241] Below, preferred embodiments will be proposed to facilitate understanding of the present invention, but these embodiments are provided only to illustrate the present invention, and it is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical concept of the present invention. Naturally, such changes and modifications also fall within the appended claims.
[0242] <Preparation Example>
[0243] <Preparation of Negative Electrode Active Materials of Examples 1 to 6>
[0244] After the chemical reaction, the silane gas is deposited on the substrate to form a silicon-based active material. Thereafter, a silicon oxide coating is formed on the surface of the silicon-based active material using the method shown in Table 1 below.
[0245] <Preparation of Negative Electrode Active Material of Comparative Example 1>
[0246] A negative electrode active material was prepared in the same manner as in Example 1, except that the silicon oxide coating layer was not formed.
[0247] <Preparation of Negative Electrode Active Material of Comparative Example 2>
[0248] After the chemical reaction, the silane gas is deposited on the substrate to form a silicon-based active material. Afterwards, a silicon oxide coating is formed on the surface of the silicon-based active material using the method shown in Table 1 below. In this case, the silicon oxide coating is subjected to an alkali treatment after heat treatment oxidation, and after the oxide coating is formed, the O content in the oxide layer is reduced by a strong alkali treatment to prepare a negative electrode active material.
[0249] For reference, the crystallinity of the silicon oxide coating layer in Table 1 below corresponds to a process of confirming whether the formed oxide layer exhibits a crystalline structure through XRD measurement.
[0250]
[0251] <Preparation of negative electrode>
[0252] A negative electrode slurry (solid content concentration: 25 wt %) was prepared by adding a negative electrode active material including the silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder to distilled water as a negative electrode slurry forming solvent at a weight ratio of 80:9.6:0.4:10.
[0253] Specifically, the first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is SWCNT.
[0254] As a specific mixing method, after the first conductive material, the second conductive material, the binder and water were dispersed at 2500 rpm for 30 minutes using a homomixer, the silicon-based active material was added thereto, and then the resulting mixture was dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.
[0255] Both surfaces of a copper current collector (thickness: 8 μm) as a negative electrode current collector layer were treated with 85 mg / 25 cm 2 The negative electrode slurry was coated with a loading amount of , and the resulting product was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 33 μm), which was used as a negative electrode (thickness of the negative electrode: 41 μm, porosity of the negative electrode 40.0%).
[0256] <Manufacturing of Secondary Battery>
[0257] By using LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry in a weight ratio of 97:1.5:1.5 to prepare a positive electrode slurry (solid concentration of 78 wt %).
[0258] On both surfaces of an aluminum current collector (thickness: 12 μm) as a positive electrode current collector, 537 mg / 25 cm 2 The positive electrode slurry was coated with a loading amount of , and the resulting product was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm), thereby preparing a positive electrode (the thickness of the positive electrode: 77 μm, the porosity is 26%).
[0259] A polyethylene separator was inserted between the positive electrode and the negative electrode of the example and the comparative example, and an electrolyte was injected therein to prepare a lithium secondary battery.
[0260] The electrolyte is obtained by adding 3 wt % of vinylene carbonate based on the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) are mixed in a volume ratio of 10:90, and adding LiPF6 as a lithium salt at a concentration of 1 M thereto.
[0261] <Experimental example>
[0262] Experimental Example 1: Evaluation of Single Battery Life
[0263] The secondary battery comprising the negative electrode manufactured in the embodiment and the comparative example was evaluated for service life using an electrochemical charger and discharger, and the capacity retention rate was evaluated. The secondary battery was subjected to an in-situ cycle test at 4.2-3.0 V 1 C / 0.5 C, and during the test, the capacity retention rate was measured by charging and discharging the secondary battery at 0.33 C / 0.33 C (4.2-3.0 V) every 50 cycles, and the results are shown in Table 2.
[0264] Capacity retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the 1st cycle)} × 100
[0265]
[0266] Experimental Example 2: 2.5 C discharge resistance increase rate at SOC50 (after 200 cycles)
[0267] During the test in Experimental Example 1, after measuring the capacity retention rate by charging and discharging the secondary battery at 0.33 C / 0.33 C (4.2-3.0 V) every 50 cycles, the resistance was measured by discharging the secondary battery at 2.5 C pulse at SOC50 to compare and analyze the resistance increase rate.
[0268] Regarding the evaluation of the resistance increase rate, the data at 200 cycles were calculated and the results are shown in Table 3 below.
[0269]
[0270] Experimental Example 3: Volume change due to 40°C gas generation using bag test
[0271] After 20 g of each of the negative electrode slurries prepared in the embodiment and the comparative example were put into a bag, the bag was sealed and stored in an oven at 40° C., and then a measuring cylinder was used to measure the change in volume over time. The results are shown in Table 4 below.
[0272]
[0273] From the above Tables 2 and 3, it can be confirmed that in the case of Examples 1 to 6 in which the silicon oxide coating according to the present application is formed, the service life evaluation and the resistance increase rate are higher than or the same as those of Comparative Examples 1 and 2. This corresponds to the results when the silicon-based active material according to the present application is used, that is, a uniform reaction can be performed during the insertion and extraction reaction of lithium during charge and discharge, and the stress applied to the silicon-based active material can be reduced to alleviate particle breakage, thereby improving the capacity retention rate of the electrode.
[0274] In addition, in the case of Examples 1 to 6 in which the silicon oxide coating according to the present application is formed, the amount of gas generated is reduced compared to Comparative Examples 1 and 2 in which the silicon oxide coating is not formed, so it can be seen from Table 4 that the volume change is lower than that of Comparative Examples 1 and 2.
[0275] This corresponds to the result that the contact between the negative electrode active material according to the present application and water in the slurry state is blocked, thereby reducing gas generation.
[0276] In addition, Comparative Example 2 corresponds to the case where the silicon oxide layer is treated with an alkali to adjust the ratio of O so as to correspond to a range lower than the present application. In this case, it can be confirmed that the degradation of the gas generation suppression effect occurs due to the formation of defects in the silicon oxide coating layer, and thus it can be confirmed that the experimental results exhibited are similar to those of Comparative Example 1 in which the silicon oxide coating layer is not applied.
Claims
1. A negative electrode active material, the negative electrode active material comprising: A silicon-based active material; and A silicon oxide coating surrounding at least a part of the outer surface of the silicon-based active material, in, Based on 100% of all atoms contained in the silicon oxide coating, the oxygen (O) atom content in the silicon oxide coating is 40% or more, and The silicon-based active material contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 70 parts by weight or more.
2. The negative electrode active material according to claim 1, wherein the thickness of the silicon oxide coating is 1 nm or more and 3 μm or less.
3. The negative electrode active material according to claim 1, wherein the grain size of the silicon-based active material is 200 nm or less.
4. The negative electrode active material according to claim 1, wherein the average particle size (D50) of the silicon-based active material is 3 μm to 10 μm.
5. The negative electrode active material according to claim 1, wherein based on 100% of all atoms contained in the silicon oxide coating, the oxygen (O) atom content in the silicon oxide coating is 60% or more.
6. The negative electrode active material according to claim 1, wherein based on the outer surface of the silicon-based active material, the area of the silicon oxide coating is 90% or more.
7. The negative electrode active material according to claim 1, wherein the silicon oxide coating contains one or more selected from the group consisting of crystalline silicon and amorphous silicon.
8. A method for preparing the negative electrode active material according to any one of claims 1 to 7, the method comprising: Depositing a silicon-based active material onto a substrate by a chemical reaction of a silane gas; Obtaining the silicon-based active material deposited on the substrate; And Forming a silicon oxide on the surface of the silicon-based active material, Wherein the forming of the silicon oxide includes: oxidizing the silicon-based active material by heat treatment or chemical treatment; Or coating the surface of the silicon-based active material with a silicon oxide, The negative electrode active material comprises a silicon oxide coating surrounding at least a part of the outer surface of the silicon-based active material, and Based on 100% of all atoms contained in the silicon oxide coating, the oxygen (O) atom content in the silicon oxide coating is 40% or more.
9. The method according to claim 8, wherein the silane gas contains one or more gases selected from monosilane, dichlorosilane, and trichlorosilane.
10. The method according to claim 8, wherein the depositing of the silicon-based active material onto the substrate by a chemical reaction of the silane gas is carried out under high temperature conditions of 100 °C or more.
11. A negative electrode composition, the negative electrode composition comprising: The negative electrode active material according to any one of claims 1 to 7; A negative electrode conductive material; and A negative electrode binder.
12. The negative electrode composition according to claim 11, wherein based on 100 parts by weight of the negative electrode composition, the content of the negative electrode active material is 60 parts by weight or more. 13 . The negative electrode composition according to claim 11 , wherein the negative electrode conductive material comprises at least one selected from the group consisting of a point conductive material, a surface conductive material, and a line conductive material.
14. A negative electrode for a lithium secondary battery, the negative electrode comprising: a negative electrode current collector layer; and A negative electrode active material layer is provided on one surface or both surfaces of the negative electrode current collector layer, The negative electrode active material layer comprises the negative electrode composition according to claim 11 or a cured product thereof.
15. The negative electrode for a lithium secondary battery according to claim 14, wherein The thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and The thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.
16. A lithium secondary battery, comprising: positive electrode; The negative electrode for a lithium secondary battery according to claim 14; A separator disposed between the positive electrode and the negative electrode; and Electrolytes.
Citation Information
Patent Citations
Coping method presentation system, coping method presentation method and recording medium
KR1020220110091A